2021
DOI: 10.1242/jeb.235820
|View full text |Cite
|
Sign up to set email alerts
|

Physiological adjustments to high foraging effort negatively affect fecundity but not final reproductive output in captive zebra finches

Abstract: Foraging at elevated rates to provision offspring is thought to be an energetically costly activity and it has been suggested that there are potentially physiological costs associated with the high workload involved. However, for the most part evidence for costs of increased foraging and/or reproductive effort is weak. Furthermore, despite some experimental evidence demonstrating negative effects of increased foraging and parental effort, the physiological mechanisms underlying costs associated with high workl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 63 publications
2
1
1
Order By: Relevance
“…Egg production in terms of egg number and mass was significantly lower under warm compared to cold ambient temperature (Figures 1B,C), which is consistent with previous findings revealing decreased egg size and mass (Williams and Cooch, 1996;Schaper and Visser, 2013) with increasing ambient temperatures (but see Griffith et al, 2020). In addition, breeding zebra finches showed decreased egg mass and clutch size when exposed to a high foraging cost feeder similar to the one we implemented (Yap et al, 2021). Here, we suggest that reduced clutch size and egg mass in the warm conditions resulted from a combination of both warm temperature and elevated foraging costs.…”
Section: Discussionsupporting
confidence: 91%
“…Egg production in terms of egg number and mass was significantly lower under warm compared to cold ambient temperature (Figures 1B,C), which is consistent with previous findings revealing decreased egg size and mass (Williams and Cooch, 1996;Schaper and Visser, 2013) with increasing ambient temperatures (but see Griffith et al, 2020). In addition, breeding zebra finches showed decreased egg mass and clutch size when exposed to a high foraging cost feeder similar to the one we implemented (Yap et al, 2021). Here, we suggest that reduced clutch size and egg mass in the warm conditions resulted from a combination of both warm temperature and elevated foraging costs.…”
Section: Discussionsupporting
confidence: 91%
“…Interestingly, despite finding sex-specific effects of energy management strategies, no sex-specific effects were found in physiological metrics in our companion study (Yap et al, 2021). In that study, we found increases in haematocrit, haemoglobin concentration and oxidative stress in response to HF treatment in both sexes.…”
Section: Discussioncontrasting
confidence: 72%
“…In that study, we found increases in haematocrit, haemoglobin concentration and oxidative stress in response to HF treatment in both sexes. However, when birds were bred in low foraging effort common garden condition following HF treatment, measures of fecundity and final reproductive output were similar between both groups (Yap et al, 2021). Taken together, findings from both the current study and the companion study suggest that daily energy expenditure and physiological metrics such as haematology and oxidative stress are at least somewhat uncoupled, as evident from the sex-specific effect and lack thereof in DEE and physiology, respectively.…”
Section: Discussionsupporting
confidence: 54%
“…Thus, the mechanism through which food availability affects reproductive success is largely an open question; in particular to what extent this effect can be attributed to direct effects, as opposed to the array of potential indirect effects. Prior studies addressed this question by either manipulating the time (Lemon 1991 ; Wiersma and Verhulst 2005 ) or the effort required per unit food (Simons et al 2014 ; Yap et al 2021 ) and found reduced food availability to decrease reproductive success, mainly by decreasing laying intervals. In our study, we used a technique we developed to mimic natural variation in food availability, by manipulating the effort required per unit food, i.e.…”
Section: Introductionmentioning
confidence: 99%